Aplikasi Maintenance Airport Rescue and Fire Fighting (ARFF) Bandar Udara Syamsudin Noor Banjarmasin Berbasis Web - Rezky Izzatul Yazidah Anwar (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Regular and effective maintenance at Airport Rescue & Fire Fighting (ARFF) at Syamsudin Noor Airport in Banjarmasin is very important to maintain the performance and reliability of the system. However, the maintenance process is often still carried out manually or using less efficient methods. Therefore, this research aims to develop a web-based ARFF maintenance application that can increase the efficiency and effectiveness of the maintenance process. From the results of research on the development of the Web-based Syamsudin Noor Banjarmasin Airport Maintenance Airport Rescue & Fire Fighting (Arff) application, conclusions can be drawn in the form of making it easier for officers/admins to search and present actual information. Makes it easier to create monthly or annual reports that include all reports that can be done efficiently.